2004
DOI: 10.1038/sj.eye.6701568
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lens design on dysphotopsia in different acrylic IOLs

Abstract: Purpose To compare the incidence and severity of all grades of dysphotopsia in three types of acrylic intraocular lenses: the Acrysof MA30 BA and MA60 BM IOLs (Alcon) and the Akreos Fit one-piece IOL (Bausch and Lomb). Methods In all 111 patients were prospectively recruited who had undergone uncomplicated cataract surgery in the previous 12 months. Patients were assessed using a combination of a questionnaire and standardised provocation test, and were scored on a grading scale of 0-6 (0 indicating no glare a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Moreover, 20.7% of patients with the Akreos IOL reported persistent dysphotopsia at 8 weeks. This is similar to the figure recently reported by Shambhu et al, 14 who found a 75% incidence of mild or no symptoms. Because their data used combined questionnaire and provocation light test criteria, it is difficult to directly correlate this with clinically relevant symptoms.…”
Section: Eight Weeks Postoperativelysupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, 20.7% of patients with the Akreos IOL reported persistent dysphotopsia at 8 weeks. This is similar to the figure recently reported by Shambhu et al, 14 who found a 75% incidence of mild or no symptoms. Because their data used combined questionnaire and provocation light test criteria, it is difficult to directly correlate this with clinically relevant symptoms.…”
Section: Eight Weeks Postoperativelysupporting
confidence: 92%
“…8 Both IOLs are square edged, although the Akreos IOL has a 50% greater edge thickness, which one would expect to be a significant factor in a positive dysphotopsia edge effect. 6,7 A previous study 14 showed the incidence of dysphotopsia to be lower with the SN60-AT IOL (68.7% asymptomatic at 8 weeks) than with MA30BA and MA60BM IOLs (48% had mild or no symptoms). As Shambhu et al 14 state, the SN60-AT is a yellow-tinted acrylic IOL with a frosted edge design, which could explain the lower incidence of dysphotopsia with this lens.…”
Section: Eight Weeks Postoperativelymentioning
confidence: 95%
See 2 more Smart Citations
“…A few years later, Erie et al 16,17 found that reflections from the front and back surfaces of equiconvex unequal biconvex designs and a higher index of refraction optic materials were also factors that increased the relative intensity of the reflected light from 300-to 3500-fold above that of the crystalline lens. Several subsequent studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] confirmed these factors to be important in producing positive dysphotopsia.…”
mentioning
confidence: 72%